Progressive Muscle Relaxation Therapy to Reduce Pain Level in Gastritis Patients: A case Study - Nur Hidayat; Ade Fitriani; Lilis Lismayanti (Inspirasi Foundation, 2023)
Introduction: Gastritis is a common gastrointestinal condition often associated with pain and discomfort. Exploring effective pain management strategies is crucial for enhancing the well-being of individuals affected by gastritis. This study investigates the potential effectiveness of progressive muscle relaxation therapy in alleviating pain among gastritis patients. Objective: This study aimed to assess the effectiveness of progressive muscle relaxation therapy in alleviating pain among patients diagnosed with gastritis. Methods: The research was conducted at BLUD RSU Banjar City from May 27 to May 31, 2022. The participant for this study was Mrs. I, a 62-year-old individual presenting complaints of pain in the left upper quadrant of the abdomen. Results: Findings from the case study indicated observable changes post-progressive muscle relaxation therapy. The patient exhibited signs of relaxation, and the pain scale, initially high, decreased to 4 within 2 days after the intervention. Further reduction to a pain scale of 2 was noted using the Numeric Rating Scale method. Conclusion: The study concludes that progressive muscle relaxation therapy exhibits promise in effectively reducing pain. Consequently, this therapeutic approach holds potential applicability in addressing acute pain issues among gastritis patients.